Extent of youth involvement in community development activities in Awka South local government area of Anambra state - Okeke, O. E. (Journal of Research in Adult and Continuing Education, 2023)
The study examined the extent of youth involvement in community development activities in Awka South Local Government Area of Anambra State. Three research questions guided the study. Descriptive survey research design was used for the study. The population of the study was made up of 82,611 youths aged 18-35 years in Awka South L.G.A. of Anambra State. A sample of 225 youths aged 18-35 years in Awka South L.G.A of Anambra State was used for the study. Accidental sampling technique was used to obtain the sample. The instrument for data collection was a researcher-developed questionnaire titled “Extent of Youth Involvement in Community Development Activities Questionnaire (EYICDAQ).” The instrument was subjected to both face and content validity by three experts. The data collected was analyzed using mean score. The study revealed that youths have been involved in community development activities such as environmental sanitation, road maintenance and security activities in Awka South L.G.A. of Anambra State to a high extent. Based on the findings of the study, the study recommended among others that community development stakeholders should see the youths as an important segment of the populace and future custodian of the community, who should be given opportunity like others, in all aspects of community development efforts such as, in the planning process, implementation, supervision and evaluation of community projects. Conclusion and implications of the study were made as well as suggestions for further studies.